Competition for land and labour among individual farms and agricultural enterprises: Evidence from Kazakhstan's grain region; Der Wettbewerb zwischen Einzelbetrieben und Agrarunternehmen um Boden und Arbeit: Einsichten aus Kasachstans Getreideregion - Martin Petrick (Leibniz Institute of Agricultural Development in Central and Eastern Europe (IAMO), 2013)
This article evaluates the recent evolution of farm structure in Kazakhstan's grain region against the reform objectives of the 1990s and the family farm theory that underpinned the latter. In the study region, super-large agroholdings, large-scale enterprises and smaller individual farms emerged side-by-side and now compete for resources in a homogenous production environment. Drawing on two survey rounds of farm-level data, we find that the agroholdings display the highest factor productivity and are the most competitive on land and labour markets among all farms. However, we also find constant technical returns to scale across farm types and a layer of smaller family farms that is highly competitive on land markets. It is thus too early to conclude that large corporate farms are economically superior to individual (family) farms. But the present analysis clearly calls into question that family farms are a per-se desirable or even the only viable way of organising agricultural production. A revision of the received family farm theory may thus be due. – – Dieser Aufsatz untersucht die Entwicklung der Betriebsstrukturen in Kasachstans Getreideregion im Lichte der Reformziele der 1990er Jahre und der Theorie des landwirtschaftlichen Familienbetriebs, die diese Ziele untermauerte. In dieser Region entstanden riesige Agroholdings, landwirtschaftliche Großbetriebe und bäuerliche Einzelwirtschaften nebeneinander. In einer homogenen Produktionsumgebung stehen sie nun im Wettbewerb um Produktionsfaktoren. Basierend auf zwei Befragungsrunden ergeben unsere Analysen, dass unter allen Betriebsformen die Agroholdings die höchste Faktorproduktivität und die größte Wettbewerbsfähigkeit auf Boden- und Arbeitsmärkten aufweisen. Allerdings belegen die Untersuchungen auch konstante Skalenerträge und die Existenz einer Gruppe kleinerer Einzelbetriebe, die ebenfalls eine hohe Zahlungsbereitschaft für Boden haben. Es erscheint daher verfrüht zu schlussfolgern, dass die juristischen Personen den Einzelbetrieben wirtschaftlich überlegen sind. Jedoch stellt die vorliegende Analyse die Sichtweise in Frage, der zufolge Familienbetriebe eine an sich wünschenswerte oder sogar die einzig lebensfähige Form der Betriebsorganisation in der Landwirtschaft seien. Eine Überprüfung der Theorie des landwirtschaftlichen Familienbetriebs scheint daher angebracht.
urn:nbn:de:gbv:3:2-27312
Keywords: O13; P32; Q12; Q15; 330; family farms; agroholdings; land market; labour market; Kazakhstan; Familienbetriebe; Bodenmarkt; Arbeitsmarkt; Kasachstan